Oligoprolines guide the self-assembly of quaterthiophenes. Issue 20 (2nd May 2019) - Ochs, Nellie A. K.; Lewandowska, Urszula; Zajaczkowski, Wojciech; Corra, Stefano; Reger, Stephan; Herdlitschka, Andreas; Schmid, Sylvia; Pisula, Wojciech; Müllen, Klaus; Bäuerle, Peter; Wennemers, Helma
Abstract : Oligoprolines of differing lengths control the self-assembly of quaterthiophenes into mono-layered or double-layered sheets, or helically twisted ribbons. Abstract : Control over the molecular organization of π-conjugated oligothiophenes into different types of supramolecular assemblies is key to their use in organic electronics but difficult to achieve as these chromophores have a pronounced tendency to aggregate. Herein we show that oligoprolines, which do not self-assemble on their own, control the self-assembly of quaterthiophenes. Spectroscopic, microscopic, and diffraction studies with quaterthiophene–oligoproline conjugates revealed the formation of mono- or double-layered sheets or, alternatively, helically twisted ribbons – depending on the length of the oligoproline. The dimensions of the nanoscopic objects, which extend into the micrometer regime, correlate with the molecular dimensions of the quaterthiophene–oligoproline building blocks.